2017
DOI: 10.1016/j.asoc.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

ProfARIMA: A profit-driven order identification algorithm for ARIMA models in sales forecasting

Abstract: In forecasting, evolutionary algorithms are often linked to existing forecasting methods to optimize their input parameters. Traditionally, the fitness function of these search heuristics is based on an accuracy measure. In this paper, however, we combine forecasting accuracy with business expertise by defining a flexible and easily interpretable profit function for sales forecasting, which is based on the profit margin of a given product, the volume of its sales and the accuracy of the forecast. ProfARIMA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…They presented that ARIMA obtains good performance in one-step and multi-step forecasting. Van Calster et al [19] developed ProfARIMA which handles the lags of a seasonal ARIMA model. They applied a developed model to the sales data of the Coca-Cola company and showed its accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They presented that ARIMA obtains good performance in one-step and multi-step forecasting. Van Calster et al [19] developed ProfARIMA which handles the lags of a seasonal ARIMA model. They applied a developed model to the sales data of the Coca-Cola company and showed its accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that ARIMA methods can be effectively combined with soft computing strategies to enhance the precision of energy forecasting model. The work in [24] has also proposed the usage of an ARIMA technique for predicting Greek electricity utilization where the planned technique in comparison with three systematic time-series methods showed better results. time series model is further proposed in [30] for short term hourly prediction for peak loads using an improved ARIMA model where the prediction results show better results over the original model.…”
Section: Technology Backgroundmentioning
confidence: 99%
“…The Autoregressive Integrated Moving Average (ARIMA) [21] is a statistical liner model for time series prediction which has been shown to be suitable for modelling short-term forecasting and has been utilized in an assortment of applications such as predicting energy demand [21], wind speed forecasting [22], vehicular traffic flow prediction [23] and sales forecasting [24]. The ARIMA model is a popular time series prediction model [25] and is well suited for monthly consumption [26] forecasting of energy usage.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction studies of ARIMA and NARNN models in other areas [2][3][4][5][6][7] found that ARIMA fits and forecasts better when the time series data shows a clear linear trend, otherwise the prediction becomes less accurate or even lower than the confidence requirements, while the NARNN model shows a better prediction performance for nonlinear changes in the data.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ARIMA, NARNN, and ARIMA-NARNN have been studied in many industries, such as agriculture and forestry [2], healthcare [3,5], geography [4], manufacturing [6], and offline retail [7]. Some of these studies [2][3][4][5] only analyzed a single time series to reach conclusions, and some [6,7] only conducted empirical analysis of the hybrid model and did not compare the ARIMA, NARNN, and ARIMA-NARNN to prove the effectiveness of the hybrid model. The innovativeness of this paper is to do a comparative study between the ARIMA, NARNN, and ARIMA-NARNN methods combining the characteristics of the e-commerce industry.…”
Section: Introductionmentioning
confidence: 99%